Clinical Outcomes of Cannulated Screws versus Ring Pin versus K-Wire with Tension Band Fixation Techniques in the Treatment of Transverse Patellar Fractures: A Case-Control Study with Minimum 2-Year Follow-Up. (16th June 2022) - Liu, Junchuan; Ge, Yiming; Zhang, Guolei; Zheng, Xuehong; Gao, Liang; Xing, Enzeng; Lu, Jiangfeng; Di, Jun; Guo, Junfei
Abstract : Purpose . K-wire with tension band (KTB) technique has long been the primary surgical method for transverse patella fractures; however, it also has shortcomings. This study is aimed at evaluating the three different techniques to see whether the cannulated screw tension band (CSTB) or ring pin tension band (RPTB) techniques could decrease complications and achieve better knee function compared with KTB. Methods . We conducted a retrospective comparison of the KTB, CSTB, and RPTB fixation techniques. We selected and reviewed 90 patients (30 patients in each fixation group) with follow-up at least 2 years. Duration of operation, intraoperative blood loss, mean healing time, visual analog scale score, range of motion, Böstman score, Iowa knee score, modified Lysholm rating scale, and postoperative complications were compared. Multivariate analyses were performed to identify the independent risk factors for fracture healing time, postoperative complications, and knee function recovery. Results . After adjusting for confounding factors, multivariate regression analysis revealed that CSTB was 0.26 times (95% CI: 0.08-0.86, p = 0.027 ) less likely to prolong fracture healing time, 0.20 times (95% CI: 0.06-0.64, p = 0.007 ) lesser risk of postoperative complications, and more than four times (95% CI: 1.41-13.56, p = 0.011 ) as likely to improve the knee function score compared with KTB. Besides, RPTB were also superior to KTB in reducing the incidence of postoperative complications (OR: 0.21, 95% CI: 0.07-0.64, p = 0.006 ) and improved knee function score (OR: 3.96, 95% CI: 1.30-12.08, p = 0.016 ); however, the CSTB group being more superior. In addition, AO/OTA C2 fractures (OR, odds ratio: 10.68, 95% CI: 1.30-87.70, p = 0.027 ) and high-energy fracture (OR: 8.78, 95% CI: 1.57-49.17, p = 0.013 ) were also associated with prolonged fracture healing time but not with postoperative complications and knee function. No significant differences in related indicators such as gender, age, BMI, AO/OTA classification, fracture side, injury mechanism, duration of operation, and intraoperative blood loss were detected among the three groups. Conclusion . This study demonstrated that the CSTB technique is superior to KTB and RPTB techniques in reducing the incidence of postoperative complications, and it also has advantages in accelerating fracture healing, achieving better VAS, ROM, and functional recovery. Further long-term large-sized prospective randomized trials are needed to evaluate the efficacy of the KTB in treating transverse patellar fractures.